The Social Justice in the Classroom Framework: A Cross-Curricular Approach to Integrate Social Justice Topics into the Classroom - Moore, Briton (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Many teachers enter the field of education with a yearning to make a difference; they have a desire to teach from a social justice perspective to help promote a better society. Most often, educators are exposed to the theories, purposes, and, approaches of such educational philosophies in their pre-service programs (Delpit, 1995). However, while these philosophies often encourage a teacher to teach from a social justice perspective, when teachers attempt to do so, they frequently run into obstacles in implementation, resulting in social justice teaching staying more theoretical than actual (Picower, 2012). This manuscript explores current theories of social justice education in order to provide teachers with a framework for implementing key concepts of teaching from a social justice perspective.